THE EFFECT OF CLINICAL PATHWAY COMPLIANCE ON THE QUALITY AND COST OF CABG PROCEDURES - Arlina, Launa Inayati; Ismawantri, Putu; Qomaruddin, Mochammad Bagus; Chalidyanto, Djazuly (Universitas Airlangga, 2025)
Abstract Background Coronary Artery Bypass Graft (CABG) is a surgical procedure with a fairly high number of cases and risks. To handle the procedure, the implementation of Clinical Pathway is required. The purpose of this study was to analyze the effect of Clinical Pathway compliance on the quality and cost of CABG procedures at Dr. Soetomo Hospital, Surabaya. Method Quantitative with an observational analytical approach, cross-sectional design. The population size was 99 medical records, with a total sampling technique of 95 medical records obtained according to the inclusion criteria, descriptive data analysis. Secondary data were obtained from medical records, incident data from the PPI Committee and the hospital's financial report in 2023. Result The average age of patients was 53 years with male gender of 80%. Compliance of officers in implementing the Clinical Pathway for CABG procedures with a compliant category 14.7%, a less compliant category 78.9% and a non-compliant category of 6.3%. There were no incidents of SSI for CABG procedures (0%). LOS of CABG procedures with length of stay ≤10 days were 70.5% and >10 days were 29.5%. Costs for CABG procedures with large Disparity (+) were 1.1%, small Disparity (+) were 54.7%, large Disparity (-) were 13.7% and small Disparity (-) were 30.5%. Conclusion There is an inverse effect between Clinical Pathway compliance and Length Of Stay (LOS), there is no effect of Clinical Pathway compliance on surgical wound infection rates and there is an effect of Clinical Pathway compliance on cost disparities.